First - principles investigation of geometry, charge and magnetic states for metal Phthalocyanine (MPc, M = Sn and Pb) molecules - N, Tsogbadrakh; S, Munkhtsetseg; Kh, Tsookhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
We have investigated the geometry, charge and magnetic states of the metal phthalocyanine (MPc, M = Sn and Pb) molecules using the first - principles method within the framework of density functional theory. We have shown that the inter - atomic bond distances of absorbed metals (M = Sn and Pb) on the Pc molecule are the different from each other due to the different atomic radii of absorbed metal atom. The absorbed metal atoms are affect to the charge state of system. The total magnetic moment generates to the metal Phthalocyanine molecules by absorbing metal atoms. PACS numbers: 31.15.E-, 31.15.Ne, 36.20.-r